Моделювання сценаріїв розвитку структури генеруючих потужностей об’єднаної енергосистеми України у період повоєнного відновлення - Shcherbyna, Evgen (General Energy Institute of the National Academy of Sciences of Ukraine, 2024)
The purpose of the study is to model possible scenarios for the transformation and development of the generating capacities structure of the Integrated Power System of Ukraine, taking into account the growing volumes of installed renewable energy capacities and losses incurred by energy facilities as a result of russian aggression, to forecast the post-war recovery and development of the country's energy sector. Two possible scenarios for the recovery and development of generating capacities are considered - in the first years of reconstruction and a few years after the end of the war. The proposed scenarios were calculated using a mathematical programming model designed to determine the optimal composition and use of capacities to cover daily electricity load schedules.